The cost of environmental policy under induced technical change - Sjak Smulders; Corrado Di Maria (Center for Economic Studies and ifo Institute (CESifo), 2012)
Conventional wisdom argues that environmental policy is less costly if environmental policy induces the development of cleaner technologies. In contrast to this argument, we show that the cost of environmental policy (a reduction in emissions) may be larger with induced technical change than without. To explain this apparent paradox, we analyze three main issues. The first key issue is whether the new technology increases or reduces the marginal cost of abatement. While most analyses in environmental economics consider it natural that marginal abatement costs fall as new technology is developed, we argue that technological change may instead increase the productivity of polluting inputs, and thus marginal abatement costs. The second issue is whether environmental policy increases or decreases total investment and innovation. Even when stricter environmental policy induces some pollution-saving technological change, it may do so at the cost of a reduced overall rate of innovation, which crowds out production and consumption, and thus makes environmental policy more costly. Finally, the presence of additional distortions drive wedges between the social and private valuation of investment and pollution that may provide incentives for induced technological change with welfare-deteriorating effects.
Keywords: H23; O38; Q55; Q58; 330; environmental policy; innovation policy; induced technical change; pollution-saving technical change; pollution-using technical change; crowding-out; second-best policy; Umweltpolitik; Umwelttechnik; Technischer Fortschritt; Umweltkosten; Innovationspolitik; Crowding out; Second Best; Theorie